A Traumatic Restorative Technique: A Review Article - Anwesha Subuddhi (Institute of Medico-legal Publications Pvt Ltd, 2020)
The art procedure is minimally invasive. It is mainly based on minimum discomfort & preservation ofmaximum healthy tooth tissue. Using hand instruments reduces pain & vibration, unlike rotary instruments.This procedure is getting more popular,acceptable in children & those individuals who fear & have anxietyabout the dental procedure insocioeconomically weaker areas are becoming more popular. Art is suggestedto utilize around the world, not only in developed countries but also in industrialized nations. This articlegives a short review of art and its uses in the current situation.